Pengaruh Metode Pembayaran QRIS Terhadap Keputusan Pembelian pada Mahasiswa Politeknik Negeri Bandung - Fahira Nur Pratiwi (International Journal Administration, Business & Organization, 2023)
The purpose of this study was to test and prove the effect of the QRIS payment method on purchasing decisions for Bandung State Polytechnic students. The population in this study were all active students at the Bandung State Polytechnic who had used QRIS with a sample of 110 respondents. The research method used is descriptive quantitative method, validity and reliability test, normality test, and simple linear regression analysis. Data collection was carried out by distributing questionnaires through the Google Form media to respondents. The results showed that the QRIS payment method had an effect on purchasing decisions for Bandung State Polytechnic students.